2019
DOI: 10.1088/1741-2552/ab131b
|View full text |Cite
|
Sign up to set email alerts
|

Thermal block of action potentials is primarily due to voltage-dependent potassium currents: a modeling study

Abstract: Objective. Thermal block of action potential conduction using infrared lasers is a new modality for manipulating neural activity. It could be used for analysis of the nervous system and for therapeutic applications. We sought to understand the mechanisms of thermal block. Approach. To analyze the mechanisms of thermal block, we studied both the original Hodgkin/Huxley model, and a version modified to more accurately match experimental data on thermal responses in the squid giant axon. Main results. Both the or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 61 publications
1
65
1
Order By: Relevance
“…The results presented in this paper support the hypothesis that the primary mechanism by which thermal block occurs is due to voltage-dependent potassium ion channels. As shown in previous modeling studies, 17,18 in response to heating, voltagedependent potassium channels in unmyelinated axons respond more rapidly than they do in unheated axons, generating a hyperpolarizing current in response to depolarizing currents. Results also suggest that sodium channels do not appear to play a significant role in establishing a thermal block.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…The results presented in this paper support the hypothesis that the primary mechanism by which thermal block occurs is due to voltage-dependent potassium ion channels. As shown in previous modeling studies, 17,18 in response to heating, voltagedependent potassium channels in unmyelinated axons respond more rapidly than they do in unheated axons, generating a hyperpolarizing current in response to depolarizing currents. Results also suggest that sodium channels do not appear to play a significant role in establishing a thermal block.…”
Section: Discussionmentioning
confidence: 51%
“…To test hypotheses derived from computational modeling studies, 18 we used a blocker of voltage-gated potassium ion channels [tetraethylammonium (TEA) chloride] and a blocker of voltage-gated sodium ion channels [tetrodotoxin (TTX)]. The formulation for TEA saline was 410 mM NaCl, 50 mM TEA, 10 mM KCl, 22 mM MgCl 2 , 33 mM MgSO 4 , 10 mM CaCl 2 , 10 mM glucose, 10 mM HEPES, pH 7.6.…”
Section: Channel Blockers and Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, while there have been many studies demonstrating IR light-mediated inhibition of APs in peripheral nerves, relatively few have investigated the resulting motor output. 20 Modeling research 22,23 showed that partially suppressed APs can resume the full waveform after leaving the localized area with elevated temperatures, while it may require a transient temperature rise of 20°C to 30°C to completely block propagating APs in single axons. 22,23 Thus, the goal of achieving motor modulation by IR light irradiation of motor nerves requires a balance between the inhibition of physiological outcomes and minimizing thermal damage to the target tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, optical components that suffice for use between 0.4 and 14 µm wavelengths to encompass visible optical and thermal infrared imaging are not readily available. Finite element heat transfer modeling and Monte Carlo simulations of photon transport in scattering media is often regarded as the benchmark approach for temperature estimation of dynamic photothermal processes in biological samples with high water concentrations (48)(49)(50)(51). Several indirect approaches have been demonstrated including temperature-dependent changes in fluorophore emission, and probe beam deflection microscopy (43,(52)(53)(54).…”
mentioning
confidence: 99%